Higher education and policy for creative economies in Africa : developing creative economies - Comunian, Roberta; Hracs, Brian J.; England, Lauren (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The book reflects on the role of the creative economies in a range of African countries (namely Ghana, Nigeria, South Africa and Kenya). Chapters explore how creative economies emerge and can be supported in African countries. The contributors focus on two key dimensions: the role of higher education and the role of policy. Firstly, they consider the role of higher education and alternative forms of specialised education to reflect on how the creative aspiration of students (and future creative workers) of these countries are met and developed. Secondly, they explore the role of policy in supporting the agendas of the creative economy, taking also into consideration the potential historical dimension of policy interventions and the impact of a lack of policy frameworks. The book concludes by reflecting on how these two pillars of creative economy development, which are usually taken for granted in studying creative economies in the global north, need to be understood with their own specificity in the context of our selected case studies in Africa. This book will be of interest to students, scholars and professionals researching the creative economies in Africa across the humanities and social sciences"--
Introduction / Roberta Comunian, Brian J. Hracs, Lauren England -- Creative higher education in Nigeria and the case of University of Lagos / Vincent Obia, Lauren England, Roberta Comunian and Duro Oni -- Collaborations for creative arts higher education delivery in Ghana: A case of the University of Cape Coast / Madinatu Bello -- Fashion Designers and education in Nairobi: challenges and opportunities / -- Lauren England, Ogake Mosomi, Roberta Comunian and Brian J. Hracs -- Uganda film and television: Creative skills development and skills gap for the sector / Roberta Comunian and Gershom Kimera -- Importance of arts and culture in community development in Nigeria: The place of the Councils for Arts and Culture / Duro Oni, Cornelius Onyekaba and Husseini Shaibu -- The historical evolution of the cultural and creative economy in Mahikeng, South Africa: Implications for contemporary policy / James Drummond and Fiona Drummond -- Finance for creative and cultural industries in Africa / Yemisi Mokuolu, Victoria Isabelle Kay, Claudia MariÌa Velilla-Zuloaga -- Developing the handicraft sector in South Africa: the role of policy / Oluwayemisi Adebola Abisuga-Oyekunle , Lauren England and Roberta Comunian -- Conclusions / Roberta Comunian, Brian J. Hracs, Lauren England.
OCLC-licensed vendor bibliographic record.
Keywords: Cultural industries -- Africa; Cultural industries -- Government policy -- Africa; Arts -- Study and teaching (Higher) -- Africa; Economic development -- Effect of education on -- Africa; BUSINESS & ECONOMICS / Industries / Media & Communications Industries